THU0325 Long-Term Outcome of Patients with Primary Antiphospholipid Syndrome: A Retrospective Multicenter Study. (15th July 2016) - Dall'ara, F.; Taraborelli, M.; Reggia, R.; Fredi, M.; Andreoli, L.; Gerosa, M.; Hoxha, A.; Massaro, L.; Tonello, M.; Cacoub, P.; Costedoat-Chalumeau, N.; Franceschini, F.; et al.
Abstract : Background: Data on the long-term outcome in primary antiphospholipid syndrome (PAPS) patients are still very limited. Objectives: To assess the long-term frequency of recurrences, organ damage, severe comorbidities, mortality and evolution in connective tissue disease (CTD) in PAPS patients. Methods: Medical records of PAPS patients followed in 6 centers for ≥15 years were retrospectively reviewed. Chi square for categorical and Student t test for continuous variables were used. P<0.05 was considered significant. Results: One hundred and fifteen patients (88% females) followed between 1983 and 2014 with a mean age at diagnosis of 33 (±10) years and mean follow-up of 19 (±3.5) years were studied. Fifty-one patients (44%) had at least a thrombotic event during follow-up for a total of 75 events and an annual incidence of 3.5%. Thromboses were more frequent in patients with previous thrombotic history (p:0.002, OR:4.8, 95%CI:1.6–14.7). There was a tendency towards anticoagulant treatment being not protective against recurrences (p:0.063). Six patients (5%) had a catastrophic event. Fifty-two women had 87 pregnancies, successful in 78% of cases. Twenty-nine percent of patients had functional damage. Damage was significantly associated with a thrombotic history (p:0.004, OR:13.9, 95%CI:1.8–288.4) and to arterial events (p<0.001, OR:7.9, 95%CI:2.7–24.3) especially stroke, but not to demographics, serology or treatment. Twenty-four major bleeding episodes were recorded in 18 patients, all on anticoagulants. Severe infections affected 6 patients (5%) with 1 fatality. A solid cancer was diagnosed in 8 patients (7%). One patient (1%) with a chronic bowel ischemia died for sepsis. Eleven percent of patients developed a CTD and 14% another autoimmune disease. Conclusions: Despite therapy, a high proportion of patients experienced new thrombotic events, while pregnancy outcome was significantly improved. Organ damage developed in a significant proportion of patients and was associated with arterial events. The risk of evolution in CTD has to be considered. Disclosure of Interest: None declared